Analog Applications of Photochemical Switches. (3rd September 2012) - Copley, Graeme; Moore, Thomas A.; Moore, Ana L.; Gust, Devens
Abstract Molecules that change their structure in response to a stimulus such as light or an added chemical can act as molecular switches. Such switches can be chemically linked to other active moieties to create molecular "devices" for various purposes. There has been much activity of late in the use of molecular switches such as photochromes in the construction of molecular logic gates that carry out binary or digital functions. However, ensembles of such molecules can also act as analog devices. Here, examples of a molecular photonic signal transducer and two mimics of photosynthetic photoregulatory processes are discussed.